2023
DOI: 10.1088/2053-1591/acece1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of melt-spun Mn-Ga-Cu-Al ribbons

Abstract: In this work, we investigated structure and magnetic properties of Mn65Ga20Al15-xCux (x = 0, 5, 10 and 15) alloy ribbons prepared by melt-spinning method combined with annealing. The annealing temperature was varied from 250°C to 350°C, and the annealing time was changed from 5 h to 20 h. Concentration of Cu and annealing process significantly influence on the formation of the desired phases in the alloy ribbons. The D022-type Mn3Ga crystalline phase with the hexagonal structure, which characterizes hard magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…More recently, manganese-based magnets, such as Mn-Ga magnets with a D0 22 phase and Mn-Bi magnets with a low-temperature phase (LTP), have been the focus of attention as prospective replacements for rare-earth magnets [17][18][19][20][21][22][23][24][25][26]. It has been reported that the Mn-Ga alloys produced by melt spinning consist of a D0 22 phase and exhibited high coercivity [27][28][29][30][31][32][33]. The advantage of Mn-Ga alloys is their high magnetocrystalline energy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, manganese-based magnets, such as Mn-Ga magnets with a D0 22 phase and Mn-Bi magnets with a low-temperature phase (LTP), have been the focus of attention as prospective replacements for rare-earth magnets [17][18][19][20][21][22][23][24][25][26]. It has been reported that the Mn-Ga alloys produced by melt spinning consist of a D0 22 phase and exhibited high coercivity [27][28][29][30][31][32][33]. The advantage of Mn-Ga alloys is their high magnetocrystalline energy.…”
Section: Introductionmentioning
confidence: 99%